Pengaruh Model Think Talk Write (TTW) Berbantuan Media Audio Visual Terhadap Kemampuan Menulis Teks Prosedur Peserta Didik Kelas IV Sekolah Dasar - Ningsih, Sulistia; Ahmad Syarif; Khairunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted based on the low procedural text writing ability of fourth-grade students due to the use of conventional teaching methods and the limited implementation of innovative learning models and instructional media. The purpose of this study was to examine the effect of the Think Talk Write (TTW) learning model assisted by audio-visual media on students’ procedural text writing skills. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 20 fourth-grade students of SDN 12/I Terusan. Data were collected through writing tests administered before (pretest) and after (posttest) the implementation of the TTW model assisted by audio-visual media. The data were analyzed using normality testing and hypothesis testing through a t-test. The findings indicated a statistically significant difference between the pretest and posttest results, demonstrating that the implementation of the Think Talk Write model assisted by audio-visual media had a significant effect on students’ procedural text writing ability. Therefore, this learning model can be considered as an alternative instructional strategy in teaching procedural text writing at the elementary school level.